The Modern US war machine an encyclopedia of American military equipment and strategy - Bonds, Ray (Salamander Books, 1987)
1987, oversize hardcover edition, Salamander Books, London, U.K., 240 pages. Magnificent detailed volume includes 500 action photos, most in color; maps, tables, charts, diagrams; and 150,000 words of informed text. This title is a definite encyclopedia of American military equipment and strategy. Includes every major weapons system employed by the American military machine.